Improved prognostic stratification of patients with pN3b oral cavity cancer based on maximum standardized uptake value of metastatic nodes, lymph node ratio, and level of cervical nodal metastases. (December 2021) - Cheng, Nai-Ming; Kang, Chung-Jan; Tsai, Chi-Ying; Lee, Li-Yu; Lin, Chien-Yu; Hsueh, Chuen; Fan, Kang-Hsing; Wang, Hung-Ming; Hsieh, Chia-Hsun; Ng, Shu-Hang; Yeh, Chih-Hua; Lin, Chih-Hung; et al.
Highlights: The prognosis of pN3b oral squamous cell carcinoma (OCSCC) remains heterogeneous. SUV-nodal-max, LNR, and level IV/V metastases were independent prognosticators. A scoring system based on these three factors improves prognostic stratification. Our results are expected to inform treatment and follow-up of this patient group. Abstract: Objectives: The prognosis of pN3b oral cavity squamous cell carcinoma (OCSCC) remains heterogeneous. We sought to improve the prognostic stratification of patients with pN3b OCSCC through a combined analysis of FDG-PET parameters and clinicopathological risk factors (RFs). Methods: From 2001 to 2019, complete data on maximum standardized uptake values derived from FDG-PET of neck metastatic nodes (SUV-nodal-max) and clinicopathological RFs were available for 257 patients with pN3b disease. Results: Using the 5-year disease-free survival (DFS) as the outcome of interest, the optimal cutoff points for SUV-nodal-max and lymph node ratio (LNR) were 15.9 and 0.17, respectively. The 5-year DFS rates/(number of cases) for patients with pN3b disease were as follows: SUV-nodal-max < 15.9 versus ≥ 15.9, 49%(2 2 6)/21%(31), p = 0.000003; LNR < 0.17 versus ≥ 0.17, 49%(2 3 0)/17%(27), p = 0.000117; absence versus presence of neck level IV/V metastases, 49%(2 3 0)/15%(27), p = 0.000004. Multivariable analyses revealed that SUV-nodal-max ≥ 15.9, LNR ≥ 0.17, and level IV/V metastases were independent prognosticators for 5-year distant metastases (DM), DFS, disease-specific survival (DSS), and overall survival (OS) rates. Based on these variables, we devised a scoring system that identified three distinct prognostic subgroups at low (score 0, n = 190), intermediate (score 1, n = 51), and high (scores 2–3, n = 16) risk. The 5-year rates of patients with pN3b disease deemed to be at low/intermediate/high risk were as follows: DM, 31%/52%/89%; DFS, 54%/26%/0%; DSS, 59%/36%/8%; OS, 42%/31%/6%, respectively; all p < 0.001. Conclusions: A scoring system based on SUV-nodal-max, LNR, and level IV/V metastases improves the prognostic stratification of OCSCC patients with pN3b disease.